Integrated metagenomic and metabolomic analyses of the effects of total flavonoids of Rhizoma Drynariae on reducing ovariectomized-induced osteoporosis by regulating gut microbiota and related metabolites - Qiuyue Li; Xuelin Wu; Xinyu Niu; Zhangjingze Yu; Shengjie Fang; Xuelei Chu; Jia Zhu; Qinghui Song; Chengzhi Hou; Xu Wei (PLoS ONE, 2025)
TFRD has been widely used in China to treat osteoporosis (OP). However, the specific molecular mechanism of TFRD against OP has not been fully clarified. Our previous studies have also proved that TFRD could attenuate OP and the clinical equivalent dose of 67.5mg/kg/d is the effective dose for TFRD treating OP. Therefore, this study used 67.5mg/kg as the dosage of TFRD in combination with multi omics to investigate the mechanism of action of TFRD in the treatment of OP. The aim of this study was to further elucidate molecular mechanism of TFRD for treating OP based on metagenomic and metabolomic analyses. In this study, hematoxylin-eosin (H&E) staining, micro computed tomography (micro-CT) and bone mineral density (BMD) analysis were used to observe pharmacological effects of TFRD against ovariectomized (OVX)-induced OP. Subsequently, multiomics analysis including metagenomics, untargeted and short chain fatty acids (SCFAs) metabolomics were carried out to identify whether the anti-osteoporosis mechanism of TFRD correlated with gut microbiota and related metabolites. Our results indicate that TFRD could improve the microstructure and density of trabecular bone in OVX rats. 17 differential species, which mainly from Akkermansia, Bacteroides, and Phascolarctobacterium genus, 14 related differential metabolites and acetic acid in SCFAs were significantly altered by OVX and reversed by TFRD. Furthermore, according to results of untargeted metabolomics analysis, it was found that several metabolic pathways such as phenylalanine metabolism, phenylalanine, tyrosine and tryptophan biosynthesis and so on might play an important role in TFRD against OP. In order to further study the relationship between gut microbiota and related metabolites, spearman correlation analysis was used, and showed that gut microbiota such as Akkermansia muciniphila might be closely related to several metabolites and metabolic pathways. These findings suggest that TFRD treatment could reduce the effects of OVX-induced OP by altering community composition and abundance of gut microbiota, regulating metabolites and SCFAs. It was speculated that the gut microbiota especially Akkermansia muciniphila and related metabolites might play an important role in TFRD against OP, and deserve further study by follow-up experiment. This conclusion provides new theoretical support for mechanism research of TFRD against OP.